Implementation of Business Judgement Rules in Indonesia: Theories, Practices, and Contemporary Cases - Irawan, Chandra Noviardy; Pujiyono, Pujiyono; Cahyaningtyas, Irma (Indonesian Journal of Advocacy and Legal Services, 2022)
Business judgment rule considerations were born with a background of problems where they are always blamed for losses suffered by the company, the impression that is built basically does not reflect the values ​​in the company’s business operations. This research aims to analyze how is the adoption process Business Judgement Rule in Indonesian law, and how to apply Business Judgement Rule in Indonesian. This research also intended to understand the application of the Business Judgment Rule doctrine in Indonesia. This research is normative juridical research conducted through library research and analyzed by qualitative research methods on the secondary data found. The results of this study indicate that the application of the Business Judgment Rule can provide legal protection for the board of directors for business policies taken even though the business policy results in losses for the company, as long as the business decisions are made with prudence, in good faith, and in the scope of authority and responsibility.